PENGARUH PENDINGINAN MEDIA AIR DAN OLI PADA HEATTREATMENT SAMBUNGAN LAS METODE SMAW TERHADAP KEKUATAN LOGAM YANG DIHASILKAN - Asep AR Ruchiyat (INOVTEK POLBENG, 2018)
Abstract Welding is a method of metal extension that utilize the Penetration of heat produced. Heat and the freeze of a metal extension is a natural phenomenon, where that process works based on the difference of temperature. The cooling temperature that work so fast creating diverse structure as the result that the mechanical ability of a metal changes.                This research purpose is to find out to what extent heat treatment with water and oil cooling media gives effect to the result of SMAW weld, considering processes changes in metal are very sensitive towards mechanical ability.                 Hardness testing in raw material that has been done gives result of 46.9 with an average hardness in the normal welding process of 48 HRB or increased by 2.34%. This value indicates that the welding process will have an impact on the increase in hardness of the weld metal. Then the weld metal heat treatment process at 850oCwith normal cooling of free air decreases the weld metal hardness by 43.5 HRB or 7.24% under raw material. While the quenching process carried out with water and oil cooler has an impact on increasing the hardness above heat treatment, normal cooling is 4.36% and 3.19% lower to the raw material. From this description it can be concluded that quench accelerates the rate of cooling and increase hardness by 4.36%. Key words: welding SMAW, heattreatment, cooling water and oil, hardness metal